Managing people in sport organizations : a strategic human resource management perspective / Tracy Taylor, Alison Doherty, and Shannon Kerwin. - Taylor, Tracy; Doherty, Alison; Kerwin, Shannon, 1981- (Sport management series., 2025)
Now in a fully revised and updated third edition, Managing People in Sport Organizations is a comprehensive introduction to the theory and practice of managing people within a strategic framework.